Identifying Communities of Concern for Older Adults Using Spatial Analysis: Focusing on Accessibility to Health, Social, and Daily Services. (November 2021) - Choi, Kwangyul; Lee, Yeonjung; Basrak, Zoe
Ensuring accessibility to necessary services is critical for older adults. However, there often exist spatial disparities in the levels of accessibility to services. Because the application of Geographic Information System (GIS) has gained attention in the gerontology field, we used spatial analysis to identify communities of concern for older adults from the perspective of accessibility. We defined the communities of concern based on the proportion of older adults and the level of accessibility to health, social, and daily services via two specific modes of transportation—walking and public transit. Our findings show that newly developed communities tend to have less accessibility to necessary services, and aging communities are randomly distributed across the city. Our results call for interdisciplinary collaboration, between urban planning and gerontology professionals, to better understand the spatial pattern of aging communities and its implication for properly addressing the mobility needs of older adults in the communities.